Close To You? How Parent–Adult Child Contact Is Influenced by Family Patterns - Deane, Glenn (J Gerontol B Psychol Sci Soc Sci, 2016)
OBJECTIVES. Intergenerational contacts occur in the context of other family relationships. We examine how in-person contacts among parents and all adult children affect each other, focusing on proximity and other predictors to assess whether and how visiting is correlated across adult children. METHODS. We use a modeling approach derived from an adaptation of multilevel models to provide a convenient mechanism by which to write child-specific equations, each with its own set of predictors, and wherein one child’s attribute values can be attached to other children’s records. RESULTS. We find that parent–adult child visiting is positively correlated across siblings, but the frequency of visiting within families is not directly reciprocated. Rather, visiting responds to common family factors. Visiting declines with distance, but there are strong discontinuities in the effect. Distance between parents and a focal child is positively associated with visiting with other children. DISCUSSION. The empirical patterns we report can be framed within enhancement and compensation models. Positive correlations and cross-sibling interactions that juxtapose levels of visiting against not seeing a child in last 12 months are consistent with the enhancement model. The cross-sibling interaction for distance, whereby one child’s farther distance leads to more visits reported with others, provides evidence of a countervailing, though, weaker, pattern of compensation for proximity.